Hubungan Tingkat Stress dengan Motivasi Belajar Mahasiswa Fakultas Kesehatan dalam Pembelajaran Online pada Masa Pandemi Covid-19 di Universitas Nurul Jadid Paiton Kabupaten Probolinggo - Nisak, Choirun; Munir, Zainal; Hafifah, Vivin Nur (Universitas Nurul Jadid, 2024)
Stress is an emotional state characterized by physical tension such as fear, anxiety, nervousness, and embarrassment when facing problems or pressure. Stress in students can arise due to remote learning during the COVID-19 pandemic. Adolescence, as a transitional period from childhood to adulthood, happens so quickly that many adolescents are often unprepared to face the challenges, including academic demands. Students experiencing academic stress tend to have maladaptive perceptions of academic demands, which may stem from the learning environment, learning materials, peer interactions, and learning abilities. This study aims to examine the relationship between stress levels and learning motivation among students during online learning in the COVID-19 pandemic at Nurul Jadid University, Paiton, Probolinggo Regency. This study used a cross-sectional method, with a total sampling technique involving 100 respondents. Data analysis using the chi-square test showed a significant relationship between stress levels and learning motivation, with a p-value of 0.000 (p<0.05). Of the 100 respondents, 52% experienced mild stress, 28% moderate stress, and 30% severe stress. This study concludes that there is a significant relationship between stress levels and learning motivation among health faculty students during online learning in the COVID-19 pandemic at Nurul Jadid University, Paiton, Probolinggo Regency.